Complexities of student dropout in higher education: a multidimensional analysis - Barragán Moreno, Sandra Patricia; González Támara, Leandro (Frontiers in Education, 2024)
Introduction Student dropout, as a dynamic and complex system, requires a broad conceptualization. The aim of this article is to analyze the concept of student dropout in higher education, with the aim of effectively addressing it at various levels, including both institutional and societal. Methods Using a mixed-methods approach, dropout patterns were traced, and a model was designed and validated using anonymized data from 17,328 students at a Colombian higher education institution offering face-to-face programs. Results Results from decision trees and survival analysis highlight the significance of economic and academic factors in increasing the risk of dropout and contributing to low graduation rates. It has been confirmed that the first two years of enrollment in the educational institution are crucial for the likelihood of dropout, and that extended time spent at the institution also increases the risk of dropout. Discussion The study highlights the dynamic complexity of student dropout and emphasizes the importance of continuously updating models by integrating diverse analysis techniques. Socioeconomic status and academic performance emerged as key factors, with a focus on students at intermediate levels.